2020
DOI: 10.1016/j.jbiotec.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Growth and lipid production of Rhodotorula glutinis R4, in comparison to other oleaginous yeasts

Abstract: Some Rhodotorula spp. have been characterized as oleaginous yeasts. Under certain culture conditions they can accumulate neutral lipids, which are mainly triglycerides (TAG). Microbial TAG that can be used as raw material for biodiesel synthesis are attractive for the biofuel industry. In this study, the ability to synthesize lipids of Rhodotorula glutinis R4, isolated in Antarctica, was compared with eight strains belonging to the genera Rhodotorula and Yarrowia with the aim of proposing a novel source of oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 43 publications
7
34
0
2
Order By: Relevance
“…The highest values of biomass (13.28 ± 0.57 to 15.78 ± 0.45 g/L), lipid production (4.51 ± 0.88 to 7.10 ± 0.85 g/L), lipid content (33.96 ± 5.72 to 47.25 ± 1.84%, w/w), Y L/x (0.340 ± 0.07 to 0.473 ± 0.03 g/g), Y x/s (0.40 ± 0.005 to 0.50 ± 0.03 g/g), Y L/s (0.17 ± 0.02 to 0.23 ± 0.01 g/g), Q x (0.10 ± 0.007 to 0.15 ± 0.004 g/L/h) and Q L (0.04 ± 0.005 to 0.08 ± 0.003 g/L/h) were reached by the oleaginous yeast strains Meyerozyma caribbica SSA1654, Meyerozyma guilliermondii SSA1547, Debaryomyces hansenii SSA1502, and Vanrija humicola SSA1514 (Table 1 ). Our findings are in agreement with those reported by Maza et al [ 54 ] who found that Rhodotorula glutinis R4, Rhodotorula toruloides Y-1091, Rhodotorula toruloides Y-6987, and Rhodotorula toruloides Y-6985 revealed the highest values of biomass (14–16 g/L), lipid production (6.8–7.3 g/L), lipid content (43.9–48.9%, w/w), Y L/x (0.45–0.50 g/g), Y x/s (0.40–0.47 g/g), Y L/s (0.18–0.22 g/g), Q x (0.119–0.134 g/L/h) and Q L (0.057–0.061 g/L/h). On the other hand, Candida viswanathii Y-E4 showed the highest lipid yield (3.55 g/L).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The highest values of biomass (13.28 ± 0.57 to 15.78 ± 0.45 g/L), lipid production (4.51 ± 0.88 to 7.10 ± 0.85 g/L), lipid content (33.96 ± 5.72 to 47.25 ± 1.84%, w/w), Y L/x (0.340 ± 0.07 to 0.473 ± 0.03 g/g), Y x/s (0.40 ± 0.005 to 0.50 ± 0.03 g/g), Y L/s (0.17 ± 0.02 to 0.23 ± 0.01 g/g), Q x (0.10 ± 0.007 to 0.15 ± 0.004 g/L/h) and Q L (0.04 ± 0.005 to 0.08 ± 0.003 g/L/h) were reached by the oleaginous yeast strains Meyerozyma caribbica SSA1654, Meyerozyma guilliermondii SSA1547, Debaryomyces hansenii SSA1502, and Vanrija humicola SSA1514 (Table 1 ). Our findings are in agreement with those reported by Maza et al [ 54 ] who found that Rhodotorula glutinis R4, Rhodotorula toruloides Y-1091, Rhodotorula toruloides Y-6987, and Rhodotorula toruloides Y-6985 revealed the highest values of biomass (14–16 g/L), lipid production (6.8–7.3 g/L), lipid content (43.9–48.9%, w/w), Y L/x (0.45–0.50 g/g), Y x/s (0.40–0.47 g/g), Y L/s (0.18–0.22 g/g), Q x (0.119–0.134 g/L/h) and Q L (0.057–0.061 g/L/h). On the other hand, Candida viswanathii Y-E4 showed the highest lipid yield (3.55 g/L).…”
Section: Resultssupporting
confidence: 94%
“…As depicted in Table 2 , various other oleaginous yeast genera, such as Cryptococcus , Cyberlindera , Candida , Cystobasidium , Rhodotorula , Rhodosporidium , and Yarrowia , have been reported to have comparable values of biomass, lipid content and lipid productivity in case of glucose or biomass waste used as a carbon source. Meyerozyma caribbica SSA1654, isolated from termite gut symbionts, showed higher lipid productivity and comparable with Rhodotorula toruloides Y-1091 [ 54 ], Rhodotorula glutinis R4 [ 54 ], Candida viswanathii Y-E4A [ 56 ], Cystobasidium oligophagum JRC1 [ 57 ], Rhodosporidium kratochvilovae HIMPA1 [ 58 ], Cryptococcus curvatus [ 59 ] , and Rhodosporidium toruloides Y4 [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…An oleaginous feedstock is generally used for the production of biodiesel and jet fuel. Low‐quality lipids are preferred, such as (i) crude vegetable oils (soybean, palm, rapeseed, and sunflower); (ii) used vegetable oils; (iii) wasted animal fats; (iv) non‐edible oils [16–19]. Currently, algae and marine organisms have been more intensively investigated as a source of TGs [20–23].…”
Section: Biomass Feedstock and Processingmentioning
confidence: 99%
“…La Antártica posee una fuente importante de levaduras oleaginosas, con adaptaciones que permiten acumular cantidades considerables de lípidos con interés biotecnológico a temperaturas entre los 15 y 25 °C (Rossi et al, 2009;Amaretti et al, 2010;Viñarta et al, 2016). Recientemente, se reportó que algunas levaduras aisladas del suelo de la Antártica contienen un alto porcentaje de ácido linoleico (omega-6) y oleico (omega-9), sugiriendo que estos microorganismos podrían tener un uso potencial en la producción de lípidos con valor comercial (Villarreal et al, 2018;Maza, Viñarta, Su, Guillamón & Aybar, 2020). Entre las levaduras oleaginosas de la Antártica, destacan las especies pertenecientes al género Rhodotorula, las cuales son excelentes productoras de ácidos grasos en forma de TAGs (Tabla II).…”
Section: Rhodotorulaunclassified
“…Entre las levaduras oleaginosas de la Antártica, destacan las especies pertenecientes al género Rhodotorula, las cuales son excelentes productoras de ácidos grasos en forma de TAGs (Tabla II). De hecho, ya se ha considerado que los TAGs de algunas cepas de Rhodotorula podrían resultar de gran utilidad como materia prima alternativa para la producción de biodiésel (Viñarta et al, 2016;Viñarta, Angelicola, Nieuwenhove, Aybar & de Figueroa, 2020;Maza et al, 2020). A pesar de que el género Rhodotorula se encuentra en varios ambientes, existen pocos estudios comparativos entre especies psicrofílicas y/o psicrotolerantes provenientes de distintos hábitats.…”
Section: Rhodotorulaunclassified